دور البنوك الإسلامية في تعزيز الشمول المالي: دراسة قياسية لعينة من الدول الإسلامية للفترة 2014 - 2021 : Role of Islamic Banks in Promoting Financial Inclusion: An Econometric Study of a Sample of Islamic Countries for the Period (2014-2021) - عثامنية فؤاد,; عمامرة ياسمينة, (Journal of North African Economies, 2025)
This research paper seeks to clarify the role of Islamic banks in promoting financial inclusion by providing a variety of banking services to all segments of society, particularly the excluded and marginalized groups, The study used sectional time series models (Panel Data) in (Eviews.12) program on a sample of 13 Islamic countries from 2014 to 2021, and the descriptive approach was used in the theoretical side and the analytical approach in the applied side. The study produced several findings, the most notable of which was the contribution of Islamic banks to increasing financial inclusion in the countries under study by providing a wide range of banking services to the largest segment of customers, It also recommends that traditional banks return to their roots and comply with Islamic law teachings in order to achieve prosperity and reduce poverty, and thus achieve high-efficiency financial inclusion